Public gardens and livable cities : partnerships connecting people, plants, and place - Rakow, Donald Andrew, 1951-; Gough, Meghan Z., 1975-; Lee, Sharon A., 1944- (Cornell University Press, 2020)
"This book asserts that challenges related to improving the livability of communities are most effectively addressed in collaboration with other organizations, and that public gardens are a critical partner for interventions using plants as the means of bringing people and communities together"--